Enhancement of penetration field in vortex matter in mesoscopic superconductors due to Andreev bound states - Dolz, Moira Ines (2019)
We study the field for the penetration of a first vortex, HP, for vortex matter nucleated in micron-sized samples with edges aligned along the nodal and antinodal directions of the d-wave superconducting order parameter of Bi2Sr2CaCu2O8-δ. Here we present evidence that the HP for vortex matter nucleated in mesoscopic samples with edges parallel to the nodal direction is larger than for the antinodal case, ∼72% at low temperatures. This finding supports the theoretical proposal that surface Andreev bound states appearing in a sample with edges parallel to the nodal direction would produce an anomalous Meissner current that increases the Bean-Livingston barrier for vortex penetration.